Endourological treatment modalities in the adult ureteropelvic junction obstruction [Erişkin üreteropelvik bileşke darliǧinda endoürolojik tedavi seçenekleri] - (:unkn) unknown (My University, 2005)
Introduction: Ureteropelvic junction obstruction (UPJ obstruction) is the insufficient expulsion of urine from renal pelvis to ureter which is caused by a congenital or acquired pathologies. MAG-3 or DTPA renal scintigraphy and rarely Whitaker test are used for the diagnosis of this disease. Open, endourologic or laparoscopic techniques can be used for the treatment of the disease. Percutaneous endopyelotomy, cautery balon endopyelotomy, ureteroscopic endopyelotomy or laparoscopic pyeloplasty are the techniques which can be used. Each of these techniques has both advantages and disadvantages. In this review, we evaluated the advantages, disadvantages, success rates and complications of endourological techniques with the support of the current literature.
Keywords: Adult; Endourologic treatment; Ureteropelvic junction obstruction